Vlijanie maksimal'noj aerobnoj proizvoditel'nosti na effektivnost' vystuplenija vysokokvalificirovannych lyžnic-gonšcic v sorevnovanijach na razlicnych distancijach - Golovachev, A. I.; Kolykhmatov, V. I.; Shirokova, S. V.; Gorbunova, E. A.; Morozov, V. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article presents the correlation dynamics between indicators of maximum aerobic performance and sports results of elite cross-country female skiers at various distances of races for the final year of Olympic training. The analysis involved the results of 18 elite female athletes specializing in various types of competitive activities, aged 20 to 27 years. The following indicators of maximal aerobic capacity were analyzed during the planned stage-by-stage comprehensive surveys program: integral indicators of physical performance (working time and maximum speed in the running treadmill test to failure), the power and efficiency of the functioning of the oxide and lactacid energy systems (MPV, VO2 max, VO2 max/kg, maximum lactate concentration). The list of goal-setting starts of the final year of the Olympic cycle included the following competitions: All-Russian competition of skiers in Tyumen, held at the end of a snowless stage of the preparatory period and associated with the completion of the basic stage snowless training (end of September), the Final of the Russia Cup and Winter Olympic Games in Pyeongchang, held in the middle of the competitive period and associated with reaching a peak (February) at the main start of the season, the Russian national championship in Syktyvkar at the end of the competition period and associated with the opportunity to be selected for the national team for the next sports season (April). The results of the correlation analysis made it possible to establish the most informative indicators of maximum aerobic performance, which determine the effectiveness of performance at different distances of the ski races included in the program of the Olympic Games and at the most significant stages of the entire sports season, among which the following races were most important: individualsprint, individual race at 10 km, skiathlon (15 km) and mass start (30 km).